Theory and Methodology of the Financial Management of the Regional Supporting University - SAZONOV, Sergey; KHARLAMOVA, Ekaterina; EZANGINA, Irina; GORSHKOVA, Natalya; KOVAZHENKOV, Mikhail; POLYANSKAYA, Elena (Journal of Advanced Research in Law and Economics; Vol 8 No 1 (2017): JARLE Volume VIII Issue 1 (23) Spring 2017, 2017)
This study focuses on the analysis and identification of specific functions and advantages of a new phenomenon in the Russian market of educational services – the regional supporting university. It is proved that the latter is the result of evolutionary actions on consolidating the existing regional organizations, provided by the relevant program federal documents. The authors recognize the adaptive system of corporate financial management as an objective basis for the effective functioning of the regional supporting university. It is established that such a system should be able to carry out the integrated planning, accounting, analysis, management and monitoring of the financial status of the university in order to maximize its profitability and achieve an acceptable level of risk and liquidity. Realizing the function of regional multifaceted innovative development, the supporting university claims the concentration of substantial budgetary sources. On the other hand, based on the example of a specific subject implementing a new model of organization, the authors note the importance of the reproduction of decentralized (equity) finances and the attraction of the resources of foundations and development institutions of the federal level on a competitive basis. The authors do not exclude the supplementation of the financing sources of the supporting university by the resources of credit infrastructure, private investors as well as regional and local budgets.